Theoretical Study of Cubic and Orthorhombic Nd1–xSrxMnO3 as a Potential Solid Oxide Fuel Cell Cathode. Issue 6 (3rd August 2015) - Zhou, Y.; Lü, Z.; Xu, S.; Xu, D.; Yang, Z.
Abstract: In this paper, the atomic and electronic structures of cubic and orthorhombic Nd1– x Sr x MnO3 are investigated using the projector augmented‐wave (PAW) methods within the spin‐polarization generalized gradient approximation (GGA+ U ), where U is on‐site Coulomb interaction correction. The optimized structure parameters of both cubic and orthorhombic bulk phases are obtained. The difference between the AFM and FM structures for NdMnO3 is very small, indicating a small magneto‐elastic effect. In Nd1– x Sr x MnO3, the pseudo‐cubic lattice constant decreases on increasing Sr doping due to the oxidation of Mn 3+ cations to the smaller Mn 4+ cations. The result of the total density of states shows the majority spin without gap and the minority spin with 4.8 × 10 −19 J gap, indicating a half‐metallic ground state for NdMnO3 in GGA+ U treatment. The Bader effective charges in both cubic and orthorhombic phases are analyzed. The oxygen vacancy formation energy of Nd1– x Sr x MnO3 becomes smaller as the Sr doping concentration increases. The oxygen vacancies can be formed more easily on Nd0.5 Sr0.5 MnO3 than other systems. These results suggest that Nd0.5 Sr0.5 MnO3 could be a promising candidate for application in SOFC.